The Pattern of Christian Medical Work in Changing India - Wilder, E. W. (International review of mission, 1959)
Explanatory Note.—Christian medical workers have for many years been concerned with the future of medical work in a free India. This question has been the main theme of the last two biennial conferences of the Christian Medical Association of India (CMAI) and its Nurses' Auxiliary. The preliminary Findings of the five study groups at the last of these conferences, at Lucknow, have been considered by groups and individuals, worked over by committees and finally adopted by the Executive Committee of the Association. They form the text of this article.